PENGARUH PENGELOLAAN DANA ALOKASI UMUM TAMBAHAN (DAU-T) TERHADAP KESEJAHTERAAN MASYARAKAT DI KELURAHAN KURANJI - Juwita Dewi Sarahwati; Iroh Rahmawati (FKIP, Universitas Banten Jaya, 2022)
The purpose of this research was to management of additional General Allocation Fund (DAU-T) conducted in accordance with financial principles, to know the welfare of the community in Kelurahan Kuranji Kecamatan Taktakan Kota Serang, to know the influence of the management of Additional General Allocation Fund (DAU-T) on the welfare of the community in Kelurahan Kuranji Kecamatan Taktakan Kota Serang. The research methods used in this research are quantitative methods, using survey techniques. The data source in this study was the source of the subject from where the data name is commonly obtained, questionnaires and interviews. The free variable in this study was The Management of Additional General Allocation Fund (DAU-T). While the variables tied in this study was Community Welfare. The subjects in this study were the entire Kelurahan Kuranji Kecamatan Taktakan Kota Serang, where the population was 4,119 and the sample numbered 100, with an error rate of 10%. The results of this study showed that there was a significant influence between the Management of Additional General Allocation Fund (DAU-T) on the welfare of the community in Kelurahan Kuranji Kecamatan Taktakan Kota Serang